Three-dimensional pore structure of activated carbon monolithic derived from hierarchically bamboo stem for supercapacitor application - Taer, Erman; Pratiwi, Lini; Apriwandi, Apriwandi; Mustika, Widya Sinta; Taslim, Rika; Agustino, Agustino (Communications in Science and Technology, 2020)
A three-dimensional pore structure on activated carbon derived from hierarchically bamboo stem was synthesized in the monolithic form for increased applicability as a supercapacitor electrode. The preparation involved two step carbonizations, using a chemical activation at different concentrations. Subsequently, the morphology, chemical content, specific surface area and pore size distribution, as well as crystalline degree were evaluated with scanning electron microscopy, energy X-ray (EDX), N2 sorption and X-ray diffraction, respectively. Therefore, cyclic voltammetry (CV) was used to assess the electrochemical performance, in a two electrode system. The result shows the significant impact of the three-dimensional structure on electrochemical performance, and the optimized sample exhibited specific capacitance of 168.8 F g-1, energy density of 23.44 Wh kg-1, and power density of 84.46 W kg-1.